INCLUSIVE EDUCATION: A PRELIMINARY STUDY AMONG TRAINEE TEACHERS IN INSTITUTE OF TEACHER EDUCATION, TECHNICAL EDUCATION CAMPUS (Proceedings of International Conference on Special Education, 2023)
In the age of globalization, Inclusive Education (IE) aims to foster engagement and provide opportunities for Students with Special Education Needs (SEN) to get involved in academic and extracurricular activities alongside mainstream students. However, there is still societal prejudice against an integrated education system that can help Students with Special Education Needs (SEN) succeed, particularly among trainee teachers. Therefore, this research was carried out to measure trainee teachers' level of understanding in terms of knowledge and readiness in implementing Inclusive Education. This study was conducted quantitatively using a survey involving 204 trainee teachers from Bachelor of Teaching Degree Program (PISMP) (June 2020, Year 3, Semester II) offered Inclusive Education course majoring in Design and Technology (RBT), Mathematics, Science, Islamic Education, Malay Studies and TESL. A set of questionnaires using 5-point Likert Scale was administered online using Google Forms and the data obtained were analysed using descriptive statistics, namely mean and standard deviation through Statistical Package for Social Science (SPSS) Version 29. The most obvious finding to emerge from the analysis is that the level of knowledge (mean=4.44, SD=0.62) and readiness (mean=4.14, SD=0.81) in understanding of Inclusive Education (IE) is high among trainee teachers in Institute of Teacher Education, Technical Education Campus (IPGKPT).The findings of this research will critically examine and provide deeper insights on improvements that can be made for both practitioners and policy-makers to achieve the goal to integrate 75% of Students with Special Education Needs (SEN) into Inclusive Education by 2025 as stated in the Malaysian Education Blueprint (2013 - 2025).